On the move : the overheating earth and the uprooting of America - Lustgarten, Abrahm (Farrar, Straus and Giroux, 2024)
A vivid, journalistic account of how climate change will make American life as we know it unfeasible. Humanity is on the precipice of a great climate migration, and Americans will not be spared. Tens of millions of people are likely to be driven from the places they call home. Poorer communities will be left behind, while growth will surge in the cities and regions most attractive to climate refugees. America will be changed utterly. Abrahm Lustgarten's On the Move is the definitive account of what this massive population shift might look like. As he shows, the United States will be rendered unrecognizable by four unstoppable forces: wildfires in the West; frequent flooding in coastal regions; extreme heat and humidity in the South; and droughts that will make farming all but impossible across much of the nation. Reporting from the front lines of climate migration, Lustgarten explains how a pattern of shortsighted policies encouraged millions to settle in vulnerable parts of the country, and introduces us to homeowners in California, insurance customers in Florida, and ranchers in Colorado who are being forced to make the agonizing choice of when, not whether, to leave. Employing the most current climate data and predictive models, he shows how America's population will be squeezed northward into a shrinking triangle of land stretching from Tennessee to Maine to the Great Lakes. The places many of us now call home are at risk, and On the Move reveals how we'll deal with the consequences. --